2023
DOI: 10.1146/annurev-genom-101422-100437
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Insights from Single-Cell Expression Quantitative Trait Loci

Abstract: Recent advancements in single-cell technologies have enabled expression quantitative trait locus (eQTL) analysis across many individuals at single-cell resolution. Compared with bulk RNA sequencing, which averages gene expression across cell types and cell states, single-cell assays capture the transcriptional states of individual cells, including fine-grained, transient, and difficult-to-isolate populations at unprecedented scale and resolution. Single-cell eQTL (sc-eQTL) mapping can identify context-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 176 publications
(251 reference statements)
0
7
0
Order By: Relevance
“…73 Characterizing human phenotypes based on cause−effect relationships between the exposome and genomic variability is a vital step that will benefit substantially from the integration of genomics and exposome research fields. The application of newer omics technologies to large biosample collections is providing unprecedented insights into human health, for example single-cell sequencing of blood samples in population-scale biobanks; 76,77 these data sets can be advantageous to the exposome field through the immune-profiling of blood cells as an indicator of an individual's past exposure to infectious agents. Qualitative proxies of exposures (for example, dietary self-reporting, smoking, and mental health questionnaires in the UK BioBank 38 ) exist in such cohorts which are beginning to be leveraged to identify GxE associations for single-exposure interactions e.g.…”
Section: ■ Opportunities To Integrate Exposome Research and Populatio...mentioning
confidence: 99%
“…73 Characterizing human phenotypes based on cause−effect relationships between the exposome and genomic variability is a vital step that will benefit substantially from the integration of genomics and exposome research fields. The application of newer omics technologies to large biosample collections is providing unprecedented insights into human health, for example single-cell sequencing of blood samples in population-scale biobanks; 76,77 these data sets can be advantageous to the exposome field through the immune-profiling of blood cells as an indicator of an individual's past exposure to infectious agents. Qualitative proxies of exposures (for example, dietary self-reporting, smoking, and mental health questionnaires in the UK BioBank 38 ) exist in such cohorts which are beginning to be leveraged to identify GxE associations for single-exposure interactions e.g.…”
Section: ■ Opportunities To Integrate Exposome Research and Populatio...mentioning
confidence: 99%
“…Genome-wide studies have identified thousands of loci that influence gene expression; these loci are known as expression quantitative trait loci or eQTLs 1,2 . eQTLs serve as an important bridge between DNA sequence variation and organismal phenotypes and provide a mechanism by which noncoding variants can underlie complex traits [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The method trains prediction models of gene expression, using genetic variants as features, to capture gene expression's cell-type or temporal specificity. Cellular state, a transient phenotype for a given cell type, can create heterogeneity within the cell type, which can limit the detection of context-dependent eQTLs 9,14,15,16 . Therefore, we also train additional prediction models after adjusting for cell state.…”
Section: Introductionmentioning
confidence: 99%